Lithium‐Ion Batteries: Suppressing Manganese Dissolution via Exposing Stable {111} Facets for High‐Performance Lithium‐Ion Oxide Cathode (Adv. Sci. 13/2019). Issue 13 (3rd July 2019) - Xiao, Yao; Zhang, Xu‐Dong; Zhu, Yan‐Fang; Wang, Peng‐Fei; Yin, Ya‐Xia; Yang, Xinan; Shi, Ji‐Lei; Liu, Jian; Li, Hongliang; Guo, Xiao‐Dong; Zhong, Ben‐He; Guo, Yu‐Guo
Abstract : In article number1801908, Yu‐Guo Guo, Xiao‐Dong Guo, and co‐workers develop a 3D hollow fusiform LiMn2 O4 cathode material with preferentially exposed stable {111} facets and seamless outer structure. The reasonable geometrical structure design suppresses manganese dissolution from the cathode/electrolyte interface and avoids the deposition of Mn 2+, resulting in excellent performance for lithium‐ion batteries.